2015
DOI: 10.3390/ijms161226108
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Caveolin-1 as Key-Regulator of Three-Dimensional Growth in Thyroid Cancer Cells Cultured under Real and Simulated Microgravity Conditions

Abstract: We recently demonstrated that the CAV1 gene was down-regulated, when poorly differentiated thyroid FTC-133 cancer cells formed spheroids under simulated microgravity conditions. Here, we present evidence that the caveolin-1 protein is involved in the inhibition of spheroid formation, when confluent monolayers are exposed to microgravity. The evidence is based on proteins detected in cells and their supernatants of the recent spaceflight experiment: “NanoRacks-CellBox-Thyroid Cancer”. The culture supernatant ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
49
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 70 publications
7
49
2
Order By: Relevance
“…PAI-1 is mainly produced by ECs, but is also secreted by other cells, e.g. thyroid cancer cells [59]. PAI-1 is involved in cancer angiogenesis, metastasis and promotes angiogenesis by stimulating EC migration toward fibronectin [60].…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1 is mainly produced by ECs, but is also secreted by other cells, e.g. thyroid cancer cells [59]. PAI-1 is involved in cancer angiogenesis, metastasis and promotes angiogenesis by stimulating EC migration toward fibronectin [60].…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis, SwissProt numbers of the investigated proteins were entered and networks built by the software based on relationships and processes from the literature, PubMed, databases and experimental data [9, 10, 33]. …”
Section: Methodsmentioning
confidence: 99%
“…Earlier experiments have shown that human thyroid cancer cells exhibit changes in the secretion of growth factors and cytokines, as well as alterations in the factors involved in 3D growth, in the cytoskeleton, and in the extracellular matrix composition when cultured in a an RPM [10, 20, 21]. Furthermore, human thyroid cells may exhibit two phenotypes in s-µ g either in the form of multicellular spheroids (MCS) or as adherent monolayer (AD) cells [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous results have demonstrated that Cav-1 is a growth-inhibitory protein that may act as a tumor suppressor (8,9). Cav-1 expression is downregulated in some forms of cancer, including mesenchymal tumors and sarcomas (8,10); however, in other cancer types; for example, oral squamous cell carcinoma, Cav-1 expression is high (11,12). These findings suggest that Cav-1 has multiple actions in human cancer cells.…”
Section: Introductionmentioning
confidence: 95%